A prospective international Aspergillus terreus survey: an EFISG, ISHAM and ECMM joint study - Risslegger, B; Zoran, T; Lackner, M; Aigner, M; Sánchez-Reus, F; Rezusta, A; Chowdhary, A; Taj-Aldeen, S J; Arendrup, M C; Oliveri, S; Kontoyiannis, D P; Alastruey-Izquierdo, A; et al. (Clinical microbiology and infection, 2017)
OBJECTIVES: A prospective international multicentre surveillance study was conducted to investigate the prevalence and amphotericin B susceptibility of Aspergillus terreus species complex infections. METHODS: A total of 370 cases from 21 countries were evaluated. RESULTS: The overall prevalence of A. terreus species complex among the investigated patients with mould-positive cultures was 5.2% (370/7116). Amphotericin B MICs ranged from 0.125 to 32 mg/L, (median 8 mg/L). CONCLUSIONS: Aspergillus terreus species complex infections cause a wide spectrum of aspergillosis and the majority of cryptic species display high amphotericin B MICs.
Keywords: lidé; amfotericin B; Aspergillosis; In vitrosusceptibility; prospektivní studie; Aspergillus; Prevalence; Evropa; Antifungal Agents; Crytic species; Humans; Microbial Sensitivity Tests; Aspergillus terreus; Prospective Studies; mikrobiální testy citlivosti; prevalence; epidemiologické monitorování; antifungální látky; Europe; Amphotericin B; Epidemiological Monitoring; aspergilóza